Pengetahuan, Kecerdasan Spiritual dan Kejadian Pernikahan Dini pada Remaja - Saputri, Dyah Ayu; Putri, Riska Hediya; Kusuma, Anggi; Surmiasih, S (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
Early marriage is a marriage carried out by a teenage couple under the age of 19 years. Based on the results of a pre-survey which conducted by the researcher in the Tanjung Bintang sub-district, there were 33 people who experienced cases of early marriage in adolescents and 33 people who did not experience cases of early marriage. The purpose of this research was to determine the correlation between knowledge and spiritual intelligence with early marriage in adolescents in Tanjung Bintang Sub-District. The design used in this research is quantitative by applying the Case-Control approach method with a comparison of case groups: Control group 1:1. The population in this research were teenagers who experienced cases of early marriage in Tanjung Bintang Sub-District, while the sample taken was 33 people in the case group: 33 people in the control group with total sampling technique. Bivariate analysis in this study used the gamma test. The results showed that the knowledge level of the case group: the control group was not good on average, namely 24 people (72.7%):15 people (45.5%). While the research result showed that the average spiritual level of cases: controls was low, namely 24 people (72.7%):14 people (42.4%). With gamma test results, the knowledge variable obtained a p-value of 0.038 (less than 0.05) and spiritual obtained a p-value of 0.035 (less than 0.05) which means that there was a correlation between knowledge and spiritual intelligence with early marriage in adolescents. The results of this research are expected to educate adolescents about early marriage knowledge and spiritual intelligence in adolescents to reduce cases of early marriage and avoid early marriage.